Selection for forage yield and quality in Crioula alfafa - de Oliveira, Paulo Ricardo Dias; Paim, Nilton Rodrigues; Czermainski, Ana Beatriz Costa (Pesquisa Agropecuaria Brasileira, 1993)
A polycross progeny test was established on Plinthosol (Polinthaquult) from April 1990 to March 1991 at EEA/UFRGS (30o05'52"S; 51o39'08"W), Eldorado do Sul, RS, Southern Brazil. The objectives were to evaluate genetic variability in a Crioula alfafa population (Medicago sativa L.), and to select plants with higher general combining ability for traits associated with forage yield and quality. The progenies showed variability for dry matter yield (DMY), plant height, growth rate, leaf to stem ratio, crude protein concentration (CPC) and crude protein yield. The estimated narrow sense heritability for DMY and CPC were 0.50 and 0.55, respectively. Predicted gains in MY and CPC from selecting the upper 20% of clones were 472 kg/ha and 1.2%, respectively. It is suggested that a synthetic cultivar be formed.
Keywords: Medicago sativa; crude protein concentration; polycross progeny test; quantitative inheritance; selection